“O ALBERGUE DAS MULHERES TRISTES” DE MARCELA SERRANO: A AUTORIA FEMININA E A FIGURA DE FLOREANA - GONÇALVES, Carolaine Balbino; FREIRE, Zélia Ramona Nolasco dos Santos² (zelianolasco@uems.br (ANAIS DO ENIC, 2023)
-